A comprehensive analysis and comparative study of the trends in thyroid cancer burden in China and globally from 1990 to 2021, with projections for the next 15 Years - Yin, Yulai; Zhang, Xiaoyu (Frontiers in Oncology, 2025)
ObjectiveThis study aims to analyze the trends in incidence, prevalence, mortality, and disability-adjusted life years (DALYs) of thyroid cancer across gender and age groups in China and globally from 1990 to 2021, using data from the Global Burden of Disease (GBD) database. Additionally, it projects the trends in thyroid cancer burden for the next 15 years for both China and the global population.Materials and methodsThyroid cancer-related data were extracted from the 2021 GBD dataset. The average annual percentage change (AAPC) and the corresponding 95% confidence intervals (95% CI) were calculated using Joinpoint regression to reflect trends in the thyroid cancer burden. R software was used to perform a gender- and age-specific analysis and visualize the trends in thyroid cancer burden for both China and the global population. Furthermore, the Autoregressive Integrated Moving Average (ARIMA) model was employed to project the trends in thyroid cancer burden over the next 15 years.ResultsThe results indicate a rising trend in the incidence and prevalence of thyroid cancer both in China and globally. Conversely, the mortality rate and DALYs show a declining trend over the same period. Age-specific analysis revealed that thyroid cancer is most prevalent among individuals aged 50–64. Gender-specific analysis indicated that the incidence rate is higher in females than in males. Projections for the next 15 years show that the age-standardized incidence rates for both males and females are expected to continue rising in China and globally. While the age-standardized mortality rate for females is projected to decline significantly, the mortality rate for males is predicted to stabilize.ConclusionBetween 1990 and 2021, the number of thyroid cancer cases has increased both in China and globally, while the mortality rate has shown a marked decline. This trend is expected to persist over the next 15 years. The growing population affected by thyroid cancer reflects a substantial disease burden, making thyroid cancer a significant global public health concern. The formulation of proactive and effective health policies is urgently needed.